2012
DOI: 10.1111/j.1365-2710.2012.01339.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic comparison of two formulations of Acarbose 100-mg tablets

Abstract: The 90% CIs of GMRs for the pharmacodynamic parameters chosen for bioequivalence evaluation of two formulations of acarbose did not meet the commonly accepted regulatory criteria for bioequivalence (0·80-1·25).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 9 publications
(12 reference statements)
2
37
1
Order By: Relevance
“…However, given that tenapanor acts locally in the gut and has minimal systemic availability, it was not appropriate or possible to evaluate the effect of food on tenapanor activity based on pharmacokinetic parameters. Therefore, the effect of food intake had to be evaluated using pharmacodynamic parameters; a similar approach has been taken in clinical pharmacology studies of other agents that act in the gut . The need to use pharmacodynamic parameters rather than pharmacokinetic parameters has also been noted when testing the bioequivalence of drugs that are locally acting and have no or minimal systemic exposure .…”
Section: Discussionmentioning
confidence: 99%
“…However, given that tenapanor acts locally in the gut and has minimal systemic availability, it was not appropriate or possible to evaluate the effect of food on tenapanor activity based on pharmacokinetic parameters. Therefore, the effect of food intake had to be evaluated using pharmacodynamic parameters; a similar approach has been taken in clinical pharmacology studies of other agents that act in the gut . The need to use pharmacodynamic parameters rather than pharmacokinetic parameters has also been noted when testing the bioequivalence of drugs that are locally acting and have no or minimal systemic exposure .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, two studies of generic acarbose in Asian countries compared locally available generic versions with the brand name. Both were bioequivalence studies, although one found irregularities within the limits allowed by the Korean drug regulatory authority [38,39].…”
Section: Studies Of Non-fda-approved Generic Versionsmentioning
confidence: 97%
“…Acarbose inhibits intestinal α-glycosidase, which decreases the digestion of ingested starch and disaccharides in the small intestine and reduces their oral absorption, resulting in decreased post-meal glucose levels (Lee et al 2012). PK endpoint method cannot be used to assess bioequivalence of acarbose tablet since its systemic exposure is negligible and the clinical efficacy is not correlated with its PK profile.…”
Section: Acarbose Tabletmentioning
confidence: 99%